'Assume the position: two queens stand before me': RuPaul as ultimate queen. Issue 4 (1st October 2020) - Collie, Hazel; Commane, Gemma
ABSTRACT: Season 10 marked a decade of RPDR, with RuPaul and other celebrities framing the show as a worldwide phenomenon promoting love, inclusivity, acceptance and Drag. This aspect of RPDR is foregrounded in much existing scholarship on the reality show which considers the inclusivity and visibility that it offers. Although RPDR brings an area of gay culture and history into the mainstream, we argue that the Queen and Herstory that is promoted and validated is RuPaul Herself. Within the show, contestants often refer to RuPaul as 'Mama Ru', in reference to historical drag family relationships. In this article, we argue that RuPaul is positioned as the Ultimate Queen rather than Drag Mother, reflecting the more transactional relationship between head judge and contestants that we argue is constructed in the show. RuPaul as Ultimate Queen is achieved through using the themes of history and authenticity to support a commodification of RuPaul which reinforces celebrity, cultural capital and authority. From Queens lip-syncing to RuPaul's back catalogue to the central place RuPaul places herself as drag pioneer; we explore 'RuPaul as commodity' and the possible implications on the presentation and marketability of gay/drag culture through the format of Drag Race and RuPaul as ultimate Queen.